Human Resource Development Practices in the Public Sector of Konso Locality - Kussia, Amanuel (African Journal of Leadership and Development, 2019)
This study examines the practices of human resource development (mainly training and development) programs in some selected public institutions of Konso district. The study employs a descriptive survey research design with a mixed approach. For the purpose of collecting primary data, a structured questionnaire with a five point Liker Scale was prepared and administered to 201 respondents drawn from sixteen public institutions. Moreover, interview was held with six key informants. Descriptive statistics such as frequency counts, percentages, mean, and tables as well as content analysis were used to present and analyze data. The findings indicated that the practices of training and development in the public institutions of the district are extremely poor. Consequently, in the majority of public organizations training and development is found to be ineffective in improving knowledge, skills, and attitudes of the employees as well as individuals and organizational performance. It is, therefore, suggested that public managers should strengthen the systems and practices of training and development, establish accountable and systematized approach to effectively manage training and development initiatives, and strengthen follow up, monitoring and evaluation mechanisms.